Diagnosis and Management of Congenital Perilymph Fistula causing Recurrent Meningitis: A Review - Rupa, Vedantam (Annals of Otology and Neurotology, 2018)
Background Congenital perilymph fistula is a rare cause of recurrent meningitis and should be suspected in any child who has had more than one episode of meningitis.Aim To define the entity of congenital perilymph fistula causing recurrent meningitis and review the literature on the subject.Methods A search was made in the PubMed database for all articles using the MeSH search terms “congenital perilymph fistula” AND “recurrent meningitis” AND “congenital perilymph fistula” AND “meningitis.”Results A total of 48 articles were obtained, of which only the relevant articles were reviewed. Diagnosis of this condition is based on typical radiological features seen on high-resolution CT scan or thin slice MRI scan of the temporal bone. A variety of congenital inner anomalies with typical radiological features may be associated with this condition. Clinical features are not diagnostic and delayed diagnosis may occur due to a low index of suspicion. All children should undergo otomicroscopic and audiological assessment too, as radiology may rarely be noncontributory. Surgical closure of these fistulae using a tympanotomy approach is successful in most patients.Conclusion Congenital perilymph fistula causing recurrent meningitis is a rare entity whose diagnosis is dependent on a high index of suspicion and appropriate radiological assessment. Surgical closure of the fistula prevents further episodes of meningitis.
Keywords: congenital perilymph fistula; inner ear anomaly; recurrent meningitis